Analysis of electrical and thermal characteristics of gapless metal oxide arresters using thermal images - Srisukkhom C. (2014)
This paper presents the electrical and thermal characteristics of distribution class - metal oxide varistor (MOV) under power frequency AC voltage changes. The leakage currents of MOV arresters are measured over a period of time against 1.0 - 2.0 p.u. of system voltage. For the experimental study, the thermal runaway property of MOV is closely related to the temperature limit which depends on the heat generation and dissipation. As the leakage current is 0.16 mA, heat generation is lower than heat dissipation. In the other hand, as the leakage current is 0.31, 0.6, and 0.8 mA, heat generation is greater than heat dissipation. The appearing of temperature distribution is observed by thermal image from thermography camera. The correlations between the electrical and thermal characteristics of MOV from the thermal image are analyzed using image processing. The developed image processing model could be used to estimate leakage current and maximum temperature of the MOV arresters. © 2011 IEEE.